A comparative kinetic study of the reaction between chromium nitrate solutions and the carboxyl groups of acetate and collage - Russell, Allan Edward (Rhodes University, Faculty of Science, Department of Chemistry, 1962)
The kinetics of the coordination reaction between the carboxyl group of the acetate radical and the trivalent chromium ion has been examined by independent methods at a temperature selected to yield reasonably accurate rate data. The study has been extended to an examination of the rate of chromium "fixation" by the carboxyl groups of hide collagen in a series of miniature tannages carried out under similar conditions for comparative purposes. The effect of olation of the chromium ions in solution on the kinetics of t he coordination reaction has also been examined. The rate of coordination of the acetate radical was followed by solvent extraction and spectrophotometric techniques over a range of concentration and pH levels. The rate data revealed a reaction having typical mass-action characteristics, the rate of reaction depending on the concentration levels of the chromium ion and the ionised acetate radical. An attempt made to distinguish a differential reaction rate in the case of a parallel reaction series using boiled and aged chromium nitrate reactant solutions, failed to reveal any significant differences between the series. The reactant solutions gave absorption spectra characteristic of the trivalent chromium ion with maxima in the 420 mµ and 570 mµ wavelength regions. The changes in optical density occurring in the vicinity of the maxima were followed spectrophotometrically, the height of the 570 mµ being found to increase during the course of reaction, while the height of the 420 mµ peak decreased. The variation in optical density at the 570 mµ peak was found to be directly related to the increase in concentration of the product complex in solution in accordance with the Baer-Bougher law, while the decrease in the height of the 420 mµ peak was related to the properties of unolated OH groups associated with the chromium complex as governed by pH and olation changes during the course of reaction. Boiled and aged chromium nitrate solutions gave reactant solutions having initial optical densities greater than those of the correspending fresh reactant solutions at the 570 mµ peak, and less than those of the fresh solutions at the 420 mµ peak. During the course of reaction, however, the two series converged to the same values. The equilibrium reaction solutions were subjected to paper electrophoretic study which indicated that all tho chromium was present in the form of cationic species. This finding was in accordance with stoicheiometric indications in the solvent extraction studies where coordination in a l : 1 ratio was reflected, giving rise to positively charged complex ions only. Making due allowance for band spreading the numbers of species predicted from the kinetic studies correspond with the electrophoretic patterns found. Application of the classical second order kinetic expression to the solvent extraction rate data, yielded plots having two distinctly linear sections, apparently indicating consecutive second order processes occurring in solution, contrary to the findings of previous workers who assign a first order mechanism to the reaction. This finding was consistent with the view that in the case of both the fresh and aged series, reaction consisted of successive coordination of an acetate radical to each chromium atom of a diol complex. Second order rate "constants" were calculated for each step and their dependency on pH level demonstrated. The findings of Hamm et al that these were first order reactions independent of acetate co'ncentration are believed to be due to their use of a large excess of acetate in their experiments. The kinetic study was further extended to an examination of the rate of "fixation"of trivalent chromium by the carboxyl groups of hide collagen under comparable conditions in a series of miniaturv tanning experiments in which the tannage substrate was provided in each of two physical forms:- (a) As hide powder where surface development was large, and (b) as prepared pelt pieces in which the fibrous weave pattern was retained. In view of the heterogeneity of the tannage systems, remarkable similarity was observed in the reaction course when compared with that of the acetate coordination studies, particularly in the case of the hide powder tannages. The dependency of the tannage rate data upon concentration and pH conditions was also found to be the same as in the case of the pure chemical system. The exact correlation between the rate data for the tannage and pure chemical systems was demonstrated by means of correlation plots. Close correlation was revealed in the case of hide powder tannage while the smaller degree of correlation observed in the case of the pelt tannage systems was attributed to the modifying effects of diffusion, particularly on the initial reaction velocity. The effect of using boiled and aged chromium solutions in the tannages was to increase the initial rate of chroniill!l "fixation" apparently due to tho coordination of a dial species at each coordination site. After the initial reaction period, the two series showed a tendency to converge as in the case of the spectrophotometric studies on the acetate reaction. The convergence trend was regarded as indicative of the tendency for the chromium in fresh solutions to under go rapid olation to the ame level as in the boiled and aged solutions. The experimental observations made on the various systems lead to the following conclusions:- (a) The mechanism of coordination of the acetate radical ttrivalent chromium appears to involve the successive coordination of ligand to each of the chromium atoms of a diol complex, both coordination steps proceeding by second order reaction mechanisms. (b) At the pH levels at which the reaction is carried out, the formation of elated bodios is rapid so that reaction in the case of both fresh and aged solutions essentially occurs between an elated species and the ionised acetate radical. (c) Modificati0ns in the absorption spectrum of the reactant solution at the 570 mµ peak are directly related to coordination, while changes at the 420 mµ peak are related to the formation of loosely-bound hydroxo chromium compounds, the concentrations of which depend on the pH level. (d) The mechanism of chromium fixation in hide is essentially similar to that operating in the case of coordination of the acetate radical to chromium, involving attachment of chromium to the side chain acid r sidues of collagen. (e ) The effect of olation is to enhance the rate of chromium fixation by hide protein during the initial reaction stages and to render possible bridge formation between adjacent side chains by secondary coordination during the latter reaction stages. (f) Where pelt pieces are used instead of hide powder, the initial rate of chromium fixation is dominated by the rate of diffusion of chromium into the fibrous structure. It should be stressed that the observations made on the various reaction systems cannot be regarded as exhaustive and the conclusions are subject to further confirmation. Consequently, the present study is essentially of a preliminary nature, but it is felt that the need for further investigation along similar lines has been demonstrated.
Keywords: Chemical kinetics; Chromium; Spectrophotometry; Electrophoresis